Managed aquifer recharge in the Marecchia alluvial fan (Rimini - Italy), start of the test and first results - Severi, Paolo; Bonzi, Luciana; Ferrari, Venusia; Pellegrino, Immacolata (Acque Sotterranee - Italian Journal of Groundwater, 2014)
Among the actions designed to manage the water crisis that have taken place in the summers of recent years in the southeastern part of the Emilia-Romagna Region, it has recently launched a trial of managed aquifer recharge in the alluvial fan of the Marecchia river (Rimini), where annually are withdrawn about 28 million m3 of water, 19 of witch for drinking water use. This test consists in conveying into quarry lake, located in the recharge area of the alluvial fan, an additional volume of water through a channel. The increase in the volume of water in the lake, should result in a rapid increase in the availability of water in the aquifers. To verify the recharge efficacy a special monitoring network consisting of 20 measuring points, 5 of which are specially drilled, it has been implemented. In 9 of these points a data logger for the continuous measure of level, temperature and electric conductivity at 20Â°C, it has been installed. A data logger has also been positioned in the channel from which the water flows into the lake. For about a month groundwater level was monitored prior to the recharge experiment. On 25 February 2014 managed aquifer recharge began and the volume of water flowing through the canal to lake until April 30, 2014, was approximately 600,000 m3. In this period it was possible to observe that the intervention produces the expected effects, thus inducing an increase in the groundwater level which is maximum near the lake and decreases away from it. The rise in the water level of the lake has been rapid and substantial. Within the area of the lake have settled some protected bird species in need of a precise environmental balance for nesting; an excessive increase of the lake level could put at risk of flooding some nests present. The objective of the following phases of the study will be to calibrate an adequate water level of the lake, to the purposes of managed aquifer recharge and to maintain the existing ecosystem. At the moment, it was decided to stop the flow of water into the lake and then to re-set it at a lower flow rate. In the test area also falls a well field that is not currently used. It will be interesting to check in the future, in the event of a major withdrawal, the influence on the progress of the flow lines in conjunction with the managed aquifer recharge.